Pemikiran Tentang Hubungan Manusia dengan Pendidikan Islam - Rudiansyah Rudiansyah; Dwi Noviani; Rani Anggraini (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The function and position of humans in this world is as a caliph on earth. The purpose of human creation in this world is to worship. While the purpose of human life in this world is to get the pleasures of this world and the peace of the hereafter. Humans are the subject of education, but also the object of education itself. The relationship between education and humans is very close.Education is a series of efforts to guide, direct the potential of human life in the form of basic abilities and learning abilities, so that changes occur in his personal life as an individual and social being and in his relationship with the surrounding environment in which he lives. The existence of education to develop human potential, towards a better human being.The caliph must have four interrelated sides of character. The four sides are fulfilling the task given by Allah, accepting the task and carrying it out in individual and group life, maintaining and managing the environment for the benefit of all, and making the duties of the caliph a guideline for its implementation.